Motor imagery profiles of the children with hemiplegic cerebral palsy according to gender and affected side (Annals of Medical Research, 2022)
Aim: The purpose of the present study is to examine the motor imagery profiles of children with hemiplegic cerebral palsy.Materials and Methods: 52 Hemiplegic (29 males, 23 females) individuals with 11.35 ± 3.48 years of mean age were included in the research. Participants’ implicit motor imagery abilities were analyzed with the laterality task. In addition, weekday and weekend screen times were questioned.Results: No statistically significant difference was determined in motor imagery abilities in terms of gender and affected extremity (p>0.05). Additionally, a significant correlation was found between screen time and Laterality task affected side accuracy and Laterality task not affected side accuracy percentages in both females and males (p
Keywords: Age; Cerebral palsy; Gender; Motor imagery; Screen time